Identification of Rare Copy Number Variants Associated With Pulmonary Atresia With Ventricular Septal Defect - Xie, Huilin; Hong, Nanchao; Zhang, Erge; Li, Fen; Sun, Kun; Yu, Yu (Frontiers in Genetics, 2019)
Copy number variants (CNVs) are major variations contributing to the gene heterogeneity of congenital heart diseases (CHD). pulmonary atresia with ventricular septal defect (PA-VSD) is a rare form of cyanotic CHD characterized by complex manifestations and the genetic determinants underlying PA-VSD are still largely unknown. We investigated rare CNVs in a recruited cohort of 100 unrelated patients with PA-VSD, PA-IVS, or TOF and a population-matched control cohort of 100 healthy children using whole-exome sequencing. Comparing rare CNVs in PA-VSD cases and that in PA-IVS or TOF positive controls, we observed twenty-two rare CNVs only in PA-VSD, five rare CNVs only in PA-VSD and TOF as well as thirteen rare CNVs only in PA-VSD and PA-IVS. Six of these CNVs were considered pathogenic or potentially pathogenic to PA-VSD: 16p11.2 del (PPP4C and TBX6), 5q35.3 del (FLT4), 5p13.1 del (RICTOR), 6p21.33 dup (TNXB), 7p15.2 del (HNRNPA2B1), and 19p13.3 dup (FGF22). The gene networks showed that four putative candidate genes for PA-VSD, PPP4C, FLT4, RICTOR, and FGF22 had strong interaction with well-known cardiac genes relevant to heart or blood vessel development. Meanwhile, the analysis of transcriptome array revealed that PPP4C and RICTOR were also significantly expressed in human embryonic heart. In conclusion, three rare novel CNVs were identified only in PA-VSD: 16p11.2 del (PPP4C), 5q35.3 del (FLT4) and 5p13.1 del (RICTOR), implicating novel candidate genes of interest for PA-VSD. Our study provided new insights into understanding for the pathogenesis of PA-VSD and helped elucidate critical genes for PA-VSD.